DIVERSITY OF INSECT THAT INTERACT WITH BALI CATTLE (Bos sondaicus) IN THE MOOR AREA AND OUTSKIRT OF FOREST - Widaswari, Kadek Wiwik; Watiniasih, Ni Luh; Suaskara, I.B. Made (Jurnal Biologi Udayana; Vol 20 No 2 (2016): Jurnal Biologi, 2016)
This study aimed to determine the types of insects that interact with bali cattle in the moor area in Kepuhvillage, District of Mendoyo, Jembrana and in the outskirts of the forest at Keladian village, Rendang, Karangasem.Samples of flying insects was taken using modified insect nets, whereas insects that patch on the surface of bodycattle were collected manualy. Collected insects were identified at the Laboratory of Ecology, Department of Biology,Udayana University. The data collected were analyzed descriptively. The results showed that the more species ofinsects (7 species) were associated with bali cattle in the outskirt of forest compared to in moor area (3 species).The temperature at the outskirt of forest was lower (average 27.6° during the day) with the average of 86.0%,compared to the average temperature of 36.0° and 65.3% of humidity during the day.
Keywords: bali cattle, insect, moor, forest, insect association